INVESTMENT AND OWNERSHIP FROM AN ISLAMIC PERSPECTIVE - Okri Handoko, Dodi; Abd. Majid, M. Shabri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Classifying ownership in the concept of standard ownership, obligations and needs in Islam, then the concept of ownership must be studied in depth, what is the Islamic view of ownership, how to invest, develop, use it and how to distribute it.Through descriptive-analytical research method by collecting primary and secondary data including books, as well as empirical facts related to the theme that the author is studying using the fiqh approach. then the two discussions become complex matters to be discussed. From here it is analyzed through literature searches, trusted sources and expert opinions in their fields.After conducting research, the author concludes that the Islamic ownership system has advantages and is in accordance with human nature because it will have an impact on justice and benefit according to the maqhosid shari'ah and the beginning is inversely proportional to the capitalist economic concept which only recognizes private ownership and the socialist economic system which only recognizes private ownership. private ownership. understand the concept of state ownership.